(untitled) (Research, Society and Development, 2021)
In the health context, several points must be taken into account to promote good quality of care. It is essential that users have all the information about the health condition they are in, and professionals who provide health care services must provide this information. Thus, we seek to identify in the literature and describe the technologies used for health education in primary health care. This is an exploratory, qualitative, descriptive, literature review, whose object of study were articles published in a form available in the Virtual Health Library. 60 articles were found related to the research criteria and 9 publications used to carry out this research. study that fit the outlined objectives. Light, light-hard and hard technologies used for health education were identified. The most described technologies are conversation wheels, presentation through lectures, dynamic games, interactive applications, in addition to websites with specific themes for health promotion.